Effect of elevated physical activity on changes in body composition and subcutaneous fat distribution in boys aged 10 to 16 years: a longitudinal study - Pastuszak, Anna; Lewandowska, Joanna; Buśko, Krzysztof; Charzewska, Jadwiga (Anthropological Review, 2014)
The study is aimed at evaluation of the effect of regular physical activity on total and subcutaneous body fat and its distribution in boys aged 10 to 16 years. A three-year longitudinal study was carried out in order to monitor physical development in 237 boys from sports schools and regular schools in Warsaw, Poland. The boys were selected so that their rate of puberty changes was similar based on evaluation of voice and facial hair. The authors measured 5 skinfolds in the following sites: triceps, calf, subscapular, suprailiac, and abdominal skinfolds. The percentage fraction of total body fat in body mass was measured by means of Tanita TBF 300 electronic body composition analyser. A limb fat to trunk fat ratio (LF/TF) was also calculated in order to evaluate the type of distribution of subcutaneous fat in boys and monitor its changes as affected by regular high physical activity throughout puberty. Lower total body fat and subcutaneous fat in boys from sports schools was the effect of considerably higher physical activity. It was demonstrated that with some minimal values of total body fat and subcutaneous fat, physical activity did not cause a reduction in body fat. It was found that elevated physical activity in boys is conducive to development of a more limb-oriented (peripheral) fatness, which is more favourable to human health.